(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The function of HR and its interaction with the marketing department are discussed in thisarticle. Despite the fact that HR Marketing are two distinct sectors, with HR caring for workers andMarketing for consumers, the article examines the relevance of both department in the business world inorder to sustain business success and culture. In order to have an influence on an organization’sperformance, it is vital to have market-oriented HR managers. HR managers should utilise the samemarketing methods that marketing managers do to sell goods and services outside of the company. As aresult, techniques that are often utilised in the external sector might be used to drive people within.